Utilização de resíduo de concreto como agregado miúdo para argamassa de concretos estruturais convencionais - Carla Adriana de Souza (2007)
In the production process of the construction area there is rubble, as in other industrial areas. However civil construction waste comes from building and demolition. This waste has become excessive and is a real problem worldwide. One solution for this problem can be to use this rubble as a recycled aggregate. Previous research has shown that recycled aggregate can be used in mortar and standard concrete. However, there are few researches to use recycled aggregates in structural concrete. Its application to structural concrete already exists however is not common yet and in the majority these researches applied just recycled coarse aggregates. Despite of the huge coarse aggregate amount, inside of rubble is possible to find a great amount of fine aggregate. An option for the recycled fine aggregate could be to replace the fine natural aggregate with the fine artificial aggregate without coarse aggregate to analyze the structural concrete behavior. The aim of this paper is to analyze the performance of the mortar of structural concrete manufactured with recycled fine aggregate. When the fine artificial replaces 25% of fine natural aggregate the results show that there arent impacts in the mechanical properties.